PERAN PEMERINTAH DESA BERAKIT DALAM MEMBERDAYAKAN MASYARAKAT MELALUI PROGRAM DESA WISATA UNTUK MENINGKATKAN KUALITAS HIDUP MASYARAKAT - Daryanti, Daryanti (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This study aims to analyze the role of the government of Berakit Village in empowering the community through the village tourism program to improve the quality of life of the community. This research uses a qualitative method with data collection techniques through observation and direct interviews with the village officials of Berakit. The results show that the role of the Berakit Village Government in formulating policies for village tourism development has been quite good. However, in the implementation stage of the program and community empowerment, its performance is still suboptimal due to several inhibiting factors that affect the success of the program. The Berakit Village Government has conducted empowerment activities in the fields of economy, youth, and religion. However, empowerment in the youth and religious sectors has not been maximized, particularly due to the lack of a youth organization that can serve as a platform for youth to actively participate in the village tourism program.